Optimalisasi Pengelolaan Wakaf Produktif Untuk Meningkatkan Kesejahteraan Umat - Zanuar Anwari; Ahmad Abrar; Gustang Gustang; Rahmawati Rahmawati; Titi Prihatin; Eko Nursalim (STIT Syekh Muhammad Nafis Tabalong, 2023)
One of the forms of worship ordered by Allah SWT is waqf, which in Islamic law means holding something for future use. Waqf is always expected to improve human welfare, therefore waqf must be maximized to achieve it. This research aims to find out how people living in Jalan Dayung 4, Sangata can live better if waqf management is optimized. To collect data in the field, this research uses interviews and documentation methods. In addition, a qualitative data analysis approach is used to collect and analyze data by starting from specific questions or facts to produce general conclusions. The results of the study show that optimizing productive waqf management can be done in several ways, one of which is by conducting partnerships. That is, the nadzir institution must carry out business cooperation between investors and capital owners who have an interest and similarity in doing waqf. Examples of partnerships that can be done are business investments with non-financial institutions and individual investments with sufficient capital.